PERAN PERAN KEMITRAAN STRATEGIS DALAM MENDORONG KEMANDIRIAN UMKM MELALUI KOLABORASI DENGAN “TOKOH RITEL” - Florida Edit Edit; Ni Wayan Widi Astuti; Putu Siti Firmani (Arthaniti Studies, 2026)
This study aims to analyze the role of strategic partnerships in promoting the independence of Micro, Small, and Medium Enterprises (MSMEs) through collaboration with retail figures. MSMEs play a crucial role in regional economic development and reducing unemployment; however, they often face challenges such as low product quality, limited innovation, and restricted market access. Strategic partnerships with retail figures are believed to help MSMEs enhance product quality, expand market reach, and strengthen economic independence.The research was conducted through a systematic analysis of data obtained from MSME actors, retail figures, and local government officials, including field observations and document studies, to understand the forms of partnership, opportunities, and challenges faced by MSMEs in improving product quality and market access. The findings indicate that strategic partnerships can significantly improve MSMEs’ product competitiveness, innovation, and market networks. However, the success of these partnerships heavily depends on a balance of power between MSMEs and retail figures, as dominance by one party may limit independence and innovation. In conclusion, effective and equitable strategic partnerships are key to strengthening MSME independence, enhancing product quality, and expanding market access, thereby supporting sustainable local economic growth